Comparison and evaluation of multiple sequence alignment tools in bininformatics - Sedaghatinia, Asieh; Atan, Rodziah; Tajul Arifin, Khairina; Azmi Murad, Masrah Azrifah (International Journal of Computer Science and Network Security, 2009)
Comparison and alignment of a series of protein and DNA sequences were among the first and are now established as the most powerful and frequently used bioinformatics methods. A variety of computational algorithms and programs have been created for this purpose. Decision about which tools to use is one of the important problems for bioinformaticians, especially for the majority of biologists who are non-specialist users. Therefore, a comparisons study for the different multiple sequence alignment tools (MSA) is necessary for the biologists and bioinformaticians to use the proper software that interprets correctly their biological data. This study addresses this critical issue in relation to MSA algorithms by systematically comparing and evaluating the functionality, usability and the algorithms of three famous multiple sequence alignment tools. A novel method was proposed for qualifying the MSA tools result by using Scorecons server to compute the conservation scores which was named SCS method (ScoreCons Server method). Furthermore, to assert the accuracy of this method for evaluating the quality of MSA tools, the results were compared with the results of SPS and CS. Finally, based on the achievement some considerations in choosing the proper MSA tools were proposed.